Synthesis of c-n powder materials by arc discharge plasma; Gas Discharge Plasmas and Their Applications (GDP 2019) - Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna (2019, 2019)
Заглавие с титульного экрана